Comparative verification of high dynamic range image tools for luminous analysis of visual environment. Issue 1 (February 2014) - Lim, Hong Soo; Kim, Jeong Tai; Kim, Gon
Design of visual environment is a complex issue involving lighting sources, luminous properties of surfaces, brightness and glare. Digital image processing software can simulate lighting designs to ensure the right amount of light and luminous quality of the visual environment. Even though there are several means about how to determine the quality of the visual environment, this study adopted high dynamic range (HDR) images captured in real-life environment. The HDR imaging has been used for research purposes to analyse discomfort glare and extract luminance on the scene. However, numbers of previous researches reveal that the capacity of HDR imaging technology for luminance acquisition might be dependent upon types of camera and the exposed ranges of images. This paper aims to verify the accuracy and pragmatic reliability of HDR image tools such as LMK and Photolux. The reflectance percentages measured by LMK and Photolux were compared to the absolute values presented by Pantone hue, value and chroma. A series of Pantone colour, yellow, warm red, rubine red, rhodamine red, purple, reflex blue, process blue and green were adopted and with varying the mixture ratio of whiteness. A variation on this type of analysis can be used to validate the design and address visual problem areas such as the detection of potential glare sources.